Delivering online community service from community perspective: A critical review - Andi Sri Wahyuni (Journal of Community Service and Empowerment, 2023)
This study presents a sharp and critical analysis of community service activities conducted by Indonesian university actors through zoom platform. Since the onset of the 2020 pandemic, community service activities have been compelled to transition to online platforms due to the necessity of maintaining social distancing. Even after the pandemic subsides, some campuses continue to engage in these activities. The research question addressed in this study is whether these methods align with the needs of the community. To answer this question, the study critically analyzes various scholarly articles that explore the implementation of community service through online teaching methods. The use of online media, such as Zoom, for community service training poses challenges from a community perspective. Firstly, it primarily benefits middle to upper-class communities who have the necessary equipment like smartphones or laptops with internet access, which contradicts the goal of reaching marginalized communities with limited resources. Secondly, the online format hinders active participation from both university and community actors, raising concerns about meaningful engagement. Moreover, selecting only a few individuals as representatives of the entire community further complicates community representation in online community service. The case studies lack clarity on how these participants effectively represent their communities and address their needs.